Commodity Markets Outlook, January 2016 - World Bank Group (World Bank, Washington, DC, 2016)
The World Bank is lowering its 2016 forecast for crude oil prices to $37 per barrel in its latest Commodity Markets Outlook report from $51 per barrel in its October projections.